THE NANOSTRUCTURED MULTIPURPOSE BIOPOLYMERS AND NANOBIOCOMPOSITES ON THEIR BASIS FOR DIAGNOSTICS AND THERAPY - B. G. Sukhov; B. A. Trofimov (Acta Biomedica Scientifica, 2012)
A novel original approach to self-organization of hybrid nanobiostructures possessing unique complex of physicochemical and biological properties (extremely demanded for noninvasive diagnosis and. therapy) is discussed.